Cognitive- and memory-enhancing effects of Augmentin in Alzheimer’s rats through regulation of gene expression and neuronal cell apoptosis - Kandeel, Mahmoud; Morsy, Mohamed A.; Abd El-Lateef, Hany M.; Marzok, Mohamed; El-Beltagi, Hossam S.; Al Khodair, Khalid M.; Albokhadaim, Ibrahim; Venugopala, Katharigatta N. (Frontiers in Pharmacology, 2023)
Alzheimer's disease (AD) is the most common type of dementia among older persons. This study looked at how Augmentin affected behavior, gene expression, and apoptosis in rats in which AD had been induced by scopolamine. The rats were divided into five groups: control, sham, memantine, Augmentin, and pre-Augmentin (the last group received Augmentin before scopolamine administration and was treated with memantine). A Morris water maze was utilized to measure spatial memory in the animals, and real-time quantitative reverse transcription PCR (qRT-PCR) and flow cytometry were employed to analyze gene expression and neuronal cell apoptosis, respectively. Memantine and Augmentin increased spatial memory in healthy rats. The use of scopolamine impaired spatial memory. Both Augmentin and memantine improved spatial memory in AD rats, particularly in the group that received memantine; however, the outcomes were more substantial when Augmentin was administered before scopolamine was given to induce AD. Furthermore, the expression of presenilin-2 (PSEN2) and inositol-trisphosphate 3-kinase B (ITPKB) increased, whereas the expression of DEAD-box helicase 5 (DDX5) fell in the AD-treated groups; however, the results were more substantial after combination therapy. According to flow cytometry studies, Augmentin pre-treatment reduced apoptosis in AD rats. The results showed that administering Augmentin to AD rats before memantine improved their spatial memory, reduced neuronal cell death, upregulated protective genes, and suppressed genes involved in AD pathogenesis.